2011
DOI: 10.1128/mcb.05242-11
|View full text |Cite
|
Sign up to set email alerts
|

Mediator Influences Telomeric Silencing and Cellular Life Span

Abstract: The Mediator complex is required for the regulated transcription of nearly all RNA polymerase II-dependent genes. Here we demonstrate a new role for Mediator which appears to be separate from its function as a transcriptional coactivator. Mediator associates directly with heterochromatin at telomeres and influences the exact boundary between active and inactive chromatin. Loss of the Mediator Med5 subunit or mutations in Med7 cause a depletion of the complex from regions located near subtelomeric X elements, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
47
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 47 publications
0
47
0
Order By: Relevance
“…Recently, a role of Mediator on telomeres was proposed, since this complex influences telomeric silencing, cellular life span, and telomere heterochromatin maintenance (Zhu et al 2011;Peng and Zhou 2012). In yeast, Mediator is bound to the telomeric regions.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a role of Mediator on telomeres was proposed, since this complex influences telomeric silencing, cellular life span, and telomere heterochromatin maintenance (Zhu et al 2011;Peng and Zhou 2012). In yeast, Mediator is bound to the telomeric regions.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptional profiling in vivo has shown that other subunits are essential for transcription of virtually all genes (20). Work in S. cerevisiae has also pointed to a role for several Mediator subunits in transcriptional repression and silencing that likely involves chromatin (21)(22)(23)(24)(25)(26)(27).…”
mentioning
confidence: 99%
“…Although the Cdk8 module is clearly involved in transcription repression (15,28), this functionality appears to be separable from those regulating chromatin, silencing, and certain forms of repression (24,26,29). Mutations in med16 (sin4) and med14 (rgr1), which lead to derepression of a subset of genes potentially through an epigenetic mechanism (30), are accompanied by gross alterations in chromatin structure in vivo (22,31).…”
mentioning
confidence: 99%
“…Transcriptional profiling in vivo shows that other Mediator subunits are essential for the transcription of virtually all genes in S. cerevisiae (18), suggesting that the complex was also a general transcription factor. Additional studies of S. cerevisiae have also pointed to a role for some Mediator subunits in transcriptional repression and silencing that likely involves chromatin (19,21,38,39,49,50).…”
mentioning
confidence: 99%